Nutritional status and sociodemographic characteristics of ‘urban poor’ school children in Onitsha, Southeast Nigeria (NIGERIAN JOURNAL OF PAEDIATRICS, 2024)
Abstract Background: The neglect of the health and nutritional status of school aged children has adverse consequences on their long term cognition and survival. Sequel to emerging issues on urbanization and the health of school children, this study focused on the nutritional status and sociodemographic characteristics of ‘urban poor’ school children in Onitsha, a major city in South East Nigeria.Objectives: The study was aimed at determining the nutritional status and evaluating the effect of certain sociodemographic factors on the nutritional status of ‘urban poor’ public primary school children in Onitsha, South East NigeriaMethod: This was a cross sectional study of 788 children aged 6 to 12 years, randomly selected from 12 public primary schools inOnitsha metropolis. Their anthropometric measures were used to determine their nutritional status. Data on their sociodemographic characteristics was obtained from their parents or caregivers using interviewer administered standardized questionnaires. Analysis was done using Microsoft Office Excel 2007, SPSS version 17 and Epiinfo version 3.5.1 software packagesResults: Stunting was the predominant form of under nutrition with a higher prevalence in the slum resident children. Greater than 60% of all the children studied were from large families with more than 4 children. Family size, however, age and gender were not significantly associated with the nutritional status of the children. Relatively though, a greater percentage of the stunted children were from large families.Conclusion: The nutritional status of ‘urban poor’ school children especially in slums in Onitsha is suboptimal compared with their counterparts in developed countries of the world. There is need for regional studies of children with similar characteristics who should be considered when favourable health policies are being made for children.